2022
DOI: 10.7554/elife.72567
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that chronic outgroup conflict reduces reproductive success in a cooperatively breeding fish

Abstract: Conflicts with conspecific outsiders are common in group-living species, from ants to primates, and are argued to be an important selective force in social evolution. However, whilst an extensive empirical literature exists on the behaviour exhibited during and immediately after interactions with rivals, only very few observational studies have considered the cumulative fitness consequences of outgroup conflict. Using a cooperatively breeding fish, the daffodil cichlid (Neolamprologus pulcher), we conducted th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 102 publications
1
4
1
Order By: Relevance
“…In contrast to previous studies of banded mongooses, chimpanzees and cichlid fish, which report negative effects of outgroup conflict on reproductive success [27][28][29], and a study of Tasmanian native hens (Tribonyx mortierii) that found no effect [56], our results indicate the possibility of a positive impact. Such interspecific variation might be related to differences in, for instance, reproductive ecology (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous studies of banded mongooses, chimpanzees and cichlid fish, which report negative effects of outgroup conflict on reproductive success [27][28][29], and a study of Tasmanian native hens (Tribonyx mortierii) that found no effect [56], our results indicate the possibility of a positive impact. Such interspecific variation might be related to differences in, for instance, reproductive ecology (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…The conflict-related improvement in dwarf mongoose pup survival is not counteracted by more infanticide or abortion, as these latter events occur only very rarely in our study population: infanticide has been observed only once, and abortion only three times, in more than 120 breeding attempts (DMRP 2011–2021, unpublished data). Our study therefore highlights the possibility that conflict with rival groups could have positive effects, not just the negative reproductive consequences previously documented [2729]; better offspring survival might arise as a by-product of conflict-induced increases in vigilance behaviour. Moreover, it showcases the need to think beyond individual contests and to assess cumulative threat when considering outgroup conflict as a social driver of fitness.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our measure of the location of a contest on each group’s territory involved calculating how much time each group spent at the contest location before the contest occurred. Using default parameters in the ctmm package (11) we first built utilization distributions (UDs) for the GPS location data of each group involved in the contest for the 90 days preceding the date of the contest (a timeframe representing a full reproductive period (12)). These UDs, which accurately account for autocorrelation in the telemetry data, represent a “familiarity index” of each grid cell (average grid cell size was 5 x 5m).…”
Section: Supporting Informationmentioning
confidence: 99%